2021
DOI: 10.2147/dddt.s318515
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of Ginkgo biloba Extract 50 and Aspirin Against Platelet Aggregation

Abstract: We aimed to investigate potential synergistic antiplatelet effects of Ginkgo biloba extract (GBE50) in combination with aspirin using in vitro models. Methods: Arachidonic acid (AA), platelet activating factor (PAF), adenosine 5ʹ-diphosphate (ADP) and collagen were used as inducers. The antiplatelet effects of GBE50, aspirin and 1:1 combination of GBE50 and aspirin were detected by microplate method using rabbit platelets. Synergy finder 2.0 was used to analyze the synergistic antiplatelet effect. The compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 76 publications
(93 reference statements)
1
26
0
Order By: Relevance
“…As a result, Gingko biloba is able to reduce platelet aggregation, and acts on the CPY2C9 and CYP3A4 isoenzymes, inhibiting the microsomial metabolism of warfarin. Therefore, herbal preparations containing Ginkgo biloba should be avoided in patients treated with antiplatelet or anticoagulant drugs [ 125 , 126 ].…”
Section: Herbal Productsmentioning
confidence: 99%
“…As a result, Gingko biloba is able to reduce platelet aggregation, and acts on the CPY2C9 and CYP3A4 isoenzymes, inhibiting the microsomial metabolism of warfarin. Therefore, herbal preparations containing Ginkgo biloba should be avoided in patients treated with antiplatelet or anticoagulant drugs [ 125 , 126 ].…”
Section: Herbal Productsmentioning
confidence: 99%
“…Furthermore, Ginkgo biloba Extract 50 (GBE50) in combination with aspirin resulted in enhanced antiplatelet effects (demonstrated through both synergistic and additive effects in restraining platelet aggregation) in vitro [ 123 ]. In addition, Ginkgo biloba extract showed antithrombotic effects on endothelial cells demonstrated through increased thrombomodulin expression and tissue-type plasminogen activator secretion in the HUVECs cell model.…”
Section: Phytochemicals With Protective Effects Against Thrombosismentioning
confidence: 99%
“…Reports have shown that ginkgolides and sesquiterpene protect mitochondria from age-related damage and improve mitochondrial function and energy metabolism [ 26 , 27 , 28 ]. There are two possible molecular mechanisms for mitochondrial protection: antagonism of platelet-activating factor receptor (PAF, 1-O-alkyl-2-acetyl-sn-glycerol-3-phosphocholine) [ 29 , 30 , 31 ] and chloride channels [ 32 , 33 , 34 ]. More than 30 genuine flavonoids are found in ginkgo biloba.…”
Section: Introductionmentioning
confidence: 99%